Chlorpyrifos subthreshold exposure induces epithelial-mesenchymal transition in breast cancer cells - Lasagna, Marianela (2021)
Chlorpyrifos (CPF) is one of the most frequently used pesticide in extensive agriculture around the world. The effects of this pesticide on carcinogenesis are not clear and there is no consensus concerning the risks of this compound. In this study we investigate whether CPF promotesepithelial-mesenchymal transition (EMT) in breast cancer cells. Migration and invasion were evaluated by wound healing assay, Boyden Chamber assay and multicellular spheroids (3D). Also, we analyzed the effects of CPF on the number and the area of first (MS1) and second (MS2)generation of MCF-7-mammospheres. We demonstrate that 50 μM CFP induces invasion in MCF-7 and MDAMB-231 cells (*** p < 0.001) when they were grown as a monolayer. In MCF-7-3D culture, we observed that 0.05 µM CPF increased the area of invasion after 7 days (** p < 0.01) and CPF at 50 µM increased the area of invasion after 5 (* p < 0.05) and 7 days (*** p < 0.001) when collagen type 1 was used as matrix model. When Matrigel® was used as substrate, we observed that only 0.05 µM CPF produced an increment of the invasion area after 2 (* p < 0.05), 5 (** p < 0.01) and 7 days (*** p < 0.001). In addition, 0.05 and 50 μM CPF increases migration in both cell lines grown as a monolayer and 3D culture. CPF at 0.05 µM induced an increment of the number and the area of MS1 and MS2 (* p < 0.05 and *** p < 0.001). Our results show that CPF promotes migration and invasion in breast cancer cells, generating a more aggressive phenotype.